Complete mitochondrial genomesequence of the hen harrier (Circus cyaneus) - Xiaodong Gao; Guolei Sun; Tian Xia; Chao Zhao; Qinguo Wei; Weilai Sha; Honghai Zhang (Mitochondrial DNA. Part B. Resources, 2018)
In this study, the complete mitochondrial genome of the Hen Harrier (Circus cyaneus) was sequenced. The genome is found to be 18,754 bp in length and has a base composition of A (31.7%), G (13.0%), C (31.2%), and T (24.1%). Similar to other Circus species, it contains a typically conserved structure including 13 protein-coding genes, 2 rRNA genes, 2 control region (D-loop), and 22 tRNA genes. A phylogenetic analysis between 17 species using 12 protein-coding genes proved that Accipiter gentilis is the most close to Circus cyaneus.